Pengaruh Gaya Kepemimpinan Terhadap Kemampuan Problem Solving Karyawan Pada Hotel Sahid Jaya Surakarta (Jurnal Sosial Humaniora dan Pendidikan, 2024)
Every company often experiences problems with both employees and customers of the company, so the company in addressing this must be wise in making decisions and finding solutions to solve problems. So the purpose of this study was to determine how much influence leadership style on problem-solving skills of employees of Hotel Sahid Jaya Surakarta. The research method used is quantitative research. The results obtained are correlated and very significant between problem solving and leadership style. A leader must have a way to solve problems, because in every sector of the company there will always be problems. The higher the problem solving, the higher the influence of the leadership style of Hotel Sahid Jaya Solo employees, and vice versa, the lower the problem solving. employees, the lower the influence of employee leadership style